Net zero targets and GHG emission reduction in the UK and Norwegian upstream oil and gas industry: A comparative assessment - Marshall Hall (The Oxford Institute for Energy Studies, 2020)
The recent adoption by the UK and Norway of 'net zero' and 'climate neutrality' targets by 2050 has galvanised the upstream oil and gas industry in both countries to adopt GHG emission reduction targets for 2030 and 2050 for the first time. Meeting these targets, ensuring an appropriate sharing of costs between investors and taxpayers and preserving investor confidence will present a lasting challenge to governments and industry. The scale of the challenge on the Norwegian Continental Shelf (NCS) is far greater than on the more mature UK Continental Shelf (UKCS) since the remaining resource base is much larger, the expected future production decline is less severe and the emission intensity on the NCS is already much lower (10 kg CO2e/boe) than on the UKCS (28 kgCO2e/boe). Norway is expected to deliver future CO2 emission reduction through an extension of its existing power-from-shore electrification programme. The high cost of such investment, borne mainly by the state via the tax system, is a political and social choice made by Norway to reduce upstream CO2 emissions without giving up its commitment to develop its remaining offshore resources. On the UKCS, the new industry target to reduce GHG emissions by 50 per cent by 2030 will require the integration of emission abatement into the OGA's MER UK strategy, well-designed economic incentives, including possibly carbon pricing and fiscal reform, and behavioural changes from operators. The relatively short remaining economic life of many mature fields and the dispersed nature of offshore power demand penalises both power-from-shore and CCS as routes to least-cost emission reduction but future integration with offshore renewable electricity generation may offer some abatement opportunities at larger installations. Methane emissions have for some years been a blind spot for government and industry on the UKCS. The UKCS has the potential to reduce methane emissions significantly from flaring, venting and leakage through better emission reporting, a more robust consents regime and changes to operating practices.
Keywords: 330; Emission Abatement; net zero emissions target; NG 164; Norwegian Continental Shelf; UK Continental Shelf; upstream GHG emissions